STRATEGI GURU BK DALAM MENINGKATKAN PRESTASI BELAJAR SISWA KELAS VII SMP YP AL-MAKSUM CINTA RAKYAT PERCUT SEI TUAN DELI SERDANG - Mahidin Mahidin; Wahyuni Wahyuni (Universitas Islam Negeri Sumatera Utara Medan, 2018)
The purpose of this study is to describe the BK teacher strategy in improving the learning achievement of Grade VII students of Al-Maksum Middle School. The method used in this study is a qualitative approach. The subjects of this study are BK teachers who have carried out services related to improving student learning achievement. The instruments used are interview guides that are systematically analyzed and collect data relating to research. Based on the results of research and data analysis, it can be concluded that the learning achievement of Grade VII students of Al-Maksum Middle School is quite good, there are only a few students who have low achievements. The reason is the lack of self-awareness of students to learn, and the inability of students to absorb some subjects. The BK teacher strategy in improving the learning achievement of Grade VII students of Al-Maksum Middle School is to approach students and create a pleasant school atmosphere so that it will be easier for the BK teacher to know the problems faced by students. Furthermore, identification and analysis of the needs / problems of students is then carried out, then the program is prepared in the form of RPL. Next is the implementation of services. Finally, an evaluation or evaluation is given to determine the extent to which an activity has been achieved and how the benefits have been done. The inhibiting factor is the implementation of guidance and counseling strategies in class VII of YP Middle School. Al-Maksum is the lack of time for service delivery, parents of students who do not support service activities, and students who do not have self-awareness to learn and no desire to change.Keywords: BK teacher strategy, student achievement